The Impact of PKM in Increasing Public Awareness of Mental Health in the Digital Era - Weraman, Pius; Fadhilah, Nurul; Lukitowati, Suci (PT. Anagata Sembagi Education, 2025)
The development of digital technology, especially social media, has changed the way individuals interact and access information, but it has also had a negative impact on mental health. Excessive use of social media is associated with an increased risk of depression, anxiety, and decreased self-esteem, especially among adolescents and young adults. In addition, gadget addiction and the phenomenon of social comparison worsen an individual's psychological condition. On the other hand, the low level of public understanding of mental health is a major challenge in efforts to prevent and treat psychological disorders. Many individuals still consider mental health problems as taboo or personal weaknesses, which prevents them from seeking help. The Student Creativity Program (PKM) can play an important role in addressing this issue by increasing public awareness through community-based education, which can be done through various digital media and interactive activities. PKM allows students to design educational programs that are socially and culturally relevant, as well as increasing mental health literacy in the community. In the context of rapidly developing digitalization, the use of technology in PKM can expand the reach of mental health education in a more interesting and effective way. Therefore, PKM has the potential to reduce the stigma of mental health and promote psychological well-being in the community.